Effect of the new nasal dilator DAN-Air® on nasal breathing and performance in elite rowers - Di Lieto, C.; Granata, D.; Ceroni Compradetti, G.; Tasca, I.; Senaldi, R.; Crisostomi, S.; Adami, P. E.; Rizzo, M.; Spataro, A. (Medicina dello Sport, 2013)
Aim. The aim of this paper was to evaluate, in elite athletes, the effect on nasal ventilation and performance of Dan-Air®, a novel commercially available device to be introduced in the nostrils which increases the nasal valve area. Methods. The study was performed on 20 male athletes of the under-23 Italian Rowing Team during the meeting preceding the U23 Word Rowing Championship 2012. All the athletes underwent an accurate anamnesis, a complete objective ENT examination and a rhinomanometry performed with Rhinopocket® at study entry, first without and subsequently with DAN-AIR. After the basal evaluation, athletes were randomly divided in two groups of 10 subjects. For 10 days athletes of group A trained with device and those of group B trained without device. At the end of this period athletes underwent a maximal 2000-meters rowing ergometer test with determination of plasma lactate and time to finish. Results. Rhinomanometry demonstrated a significant reduction of total nasal resistance with Dan-Air® and a significant increase of nasal breathing in all the athletes associated with a subjective improvement of nasal breathing. Total inspiratory NARs resulted 0.337±0.11 Pa/cm3/s without Dan-Air® and 0.159±0.13 with Dan-Air®, (Ä52.8%); total expiratory NARs resulted 0.328±0.12 Pa/cm3/s without Dan-Air® and 0.179±0.14 (Ä45.4%) with Dan-Air®. However, no significant differences were found between athletes of group A and group B in both lactate values and time to finish in the maximal rowing-ergometer test. Conclusion. Dan-Air® is effective in improving nasal ventilation in elite athletes, however, this effect does not translate in performance improvement in the short time.